A case report: remdesivir effective in the treatment of severe category COVID-19 - Pandya, Hetal; Jain, Archit; Reddy, Pradeep; Shah, Aarsh (International Journal of Research in Medical Sciences, 2020)
Since the first cases were reported in December 2019, infection with the severe acute respiratory corona virus 2 (SARS-CoV-2) has become a worldwide pandemic. COVID-19 the illness caused by SARS-CoV-2 is overwhelming health care systems globally. In the absence of a proven effective therapy, current management consists of supportive care, including invasive and noninvasive oxygen support and off-label or compassionate-use therapies, including anti-retrovirals, anti-parasitic agents, anti-inflammatory compounds, and convalescent plasma. Amongst these experimental therapies, remdesivir a broad-spectrum antiviral drug has shown some promising results. We present a successfully treated patient of severe acute respiratory illness by SARS-CoV-2 with remdesivir along with standard management protocol. Reporting a case with aim to add favoring evidence for remdesivir in the treatment of SARS-CoV-2.